Analisis Usaha Unggulan Bumdes Dengan Pendekatan Analytical Hierarchy Process (AHP) Di Desa Citangtu Kecamatan Pangatikan Kabupaten Garut - Yudiardi, Dodi; Pundenswari, Pupung; Novianti, Ega (Program Pasca Sarjana Universitas Garut, 2021)
In order to improve the economy in Indonesia, especially in villages and as a form of regional autonomy, the government issued a policy for each village to establish Village Owned Enterprises (BUMDes). Citangtu Village, is one of the areas that implemented a policy regarding BUMDes in 2015 and was established under the name